Association of High‐Sensitivity C‐Reactive Protein and Lipoprotein‐Associated Phospholipase A2 with Metabolically Unhealthy Phenotype: A Cross Sectional Study - Wang J; Yang S; Zhao L (Dove Medical Press, 2024)
Jiangang Wang,1,2 Saiqi Yang,1,2 Linlin Zhao1,2 1Health Management Center, The Third Xiangya Hospital, Central South University, Changsha, Hunan, 410013, People's Republic of China; 2Health Management Research Center of Central South University, Changsha, Hunan, 410013, People's Republic of ChinaCorrespondence: Linlin Zhao, Email Zllin7@126.comObjective: Whether the combination of high‐sensitivity C‐reactive protein (hs-CRP) and Lipoprotein‐associated Phospholipase A2 (Lp-PLA2) was an independent risk factor for metabolic unhealthy is unknown. This study aimed to evaluate the association between combining hs‐CRP and Lp‐PLA2 and metabolic unhealthy.Methods: A total of 3198 participants who underwent routine health check-up examinations. The participants completed inflammation indicators (hs-CRP and Lp-PLA2) examination and physical assessments. Four phenotypes were determined according to obesity and metabolic health status. Meanwhile, the participants were divided into four groups according to the level of hs‐CRP and Lp‐PLA2. The cross-sectional association between hs‐CRP, Lp‐PLA2 and metabolic unhealthy was tested by logistic regression analysis.Results: About 30.48%, 17.35%, 17.32% and 34.83% had MHNO, MUNO, MHO, and MUO, respectively. The combination of the hs‐CRP and Lp‐PLA2 levels was significantly correlated with metabolic unhealthy in non-obese subjects. However, in obese subjects, only hs-CRP level was significantly correlated with metabolic unhealthy.Conclusion: The hs-CRP and Lp‐PLA2 together were significantly associated with metabolic unhealthy in non-obese subjects. hs-CRP level was significantly correlated with metabolic unhealthy in obese subjects.Keywords: hs-CRP, Lp-PLA2, metabolically unhealthy, obese